Hemodynamic changes of the uterine artery in mares with different uterine pathologies - Uçmak, Zeynep Günay (Slovenian veterinary research, 2024)
Cysts, fluid accumulation, inflammatory changes and tumors are common uterine pathologies in mares. It was aimed to investigate the change of uterine hemodynamics in mares according to uterine pathologies (endometritis or intrauterine cysts). The study contained 28 mares and the groups formed as 9 gynaecologically healthy diestrus mares (Group H), 9 mares with endometritis (Group E) and 10 mares with intrauterine cyst (Group C). The mean uterine diameter (UD) in Group H (2.29±0.18 cm) was significantly lower than in Group C (2.97±0.19 cm) (P0.05). However, PI and RI values in Group H were significantly lower than both in Group E and Group C (P<0.001). The UA waveform in Group E had an early diastolic notch while systolic notches and small diastolic peaks were observed in the UA waveforms of the mares in group C. Doppler USG is considered as a useful tool to analyze the waveform and hemodynamics of the UA related to the different pathologies (cyst or endometritis). It was concluded that not only Doppler indices but also characteristics of the waveforms of the UA should be evaluated to understand the hemodynamic effect of the uterine pathologies.
Keywords: Doplerjeva ultrazvočna preiskava; Doppler ultrasonography; endometritis; intrauterina cista; intrauterine cyst; notch; zareza